Strategic Human Resource Management and Organizational Performance: A Comprehensive Review: case study about employees at Ninewells Hospital, Dundee, UK - Salim Farag Elomami, Asaad (Dirasat in Economics and Business, 2026)
Human resource management (HRM) enables making sustainable organisational performance a reality for today›s dynamic business environment. HR practice alignment and organisational strategy have been among the biggest forces driving innovation, employee engagement, and competitive success. This article presents an overview of the history of HRM from administrative work to being an organisational strategy partner and its contribution to organisational performance. Based on extensive literature review and some recent theory such as Resource-Based View (RBV) and Human Capital Theory, in this study an analysis has been presented on how strategic HR practices such as talent management, performance management, employee development, and diversity management have influence on employee›s performance along with organisational performance. The study also addresses the role of leadership, organisational culture, technology such as artificial intelligence, in trying to conceptualise HR effectiveness. For organisational leaders and HR practitioners in best practice and trends in world-class companies, implications of the study are noted. The study reiterates the importance of strategic HRM and alignment of firm strategy in response to changing labour markets and generating long-term value. Research implications are developed to build strategic competencies of HR functions, and suggestions are given for future research..